Assessment of the Effect of the Main Grain-Producing Areas Policy on China’s Food Security - Shaohua Wang; Haixia Wu; Junjie Li; Qin Xiao; Jianping Li (2024)
Food provided a material foundation for the development of human society and was an important cornerstone for ensuring national security. The Chinese government has always attached great importance to food security, which is not only related to economic development and social stability but also to national security and self-reliance. As the core region for grain production and the supply of staple food in China, the major grain-producing areas account for 78.25% of the total national grain output, truly earning the title of China’s “granary”. Considering the establishment of 13 major grain-producing regions across the country in 2004 as a quasi-natural experiment, the impact of policies in major grain-producing regions on ensuring national food security is examined using a difference-in-differences method based on inter-provincial panel data for 30 provinces across the country from 1997 to 2020, and the mechanisms of their effects are further analyzed. The findings show that (1) the main producing-areas policy has a significant driving effect on China’s food security, with an average annual increase of 0.0351 units in the food-security index, and the impact is expanding year by year. (2) The policy of the main grain-producing provinces mainly plays a role in guaranteeing food security by expanding the scale of grain cultivation and the scale of family land management in the main grain-producing provinces, and the scale effect of grain cultivation has a more significant impact. Further adjusting and improving the policy of the main grain-producing areas and expanding the scale-driven effect of this policy are of great significance for transforming agricultural production methods and realizing a strong agricultural country.